1985
DOI: 10.1007/bf00041656
|View full text |Cite
|
Sign up to set email alerts
|

Propagation in vitro of the apple rootstock M4: effect of phytohormones on shoot quality

Abstract: The quality of shoots in cultures of the apple rootstock, M4, was used as a criterion for the selection of an optimum medium. The frequency of shoots in defined shoot clases was monitored for each of five media, which differed in the type and concentration of phytohormone. Media containing BA (1.15 mgl-~) and IBA (either 0.15 or 0.20mgl -t) produced the maximum number of shoots that were desirable for transplantation and acclimatization.Abbreviations used in the text BA = Benzyl adenine (benzyl amino purine) I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1987
1987
2018
2018

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(2 citation statements)
references
References 10 publications
0
2
0
Order By: Relevance
“…In a study of Troyer citrange regeneration, it was shown that bud sprouting and subsequent shoot formation, facilitated by addition of BA, was significantly increased by light (Moreira- Dias et al 2000). According to Dunstan et al (1985) high cytokinin concentrations stimulated adventitious shoot formation but caused harmful effects on explant quality. Therefore, for further establishment of double-stage culture system, node explants were cultured under 16/8 h photoperiod and BA concentration was reduced.…”
Section: Resultsmentioning
confidence: 96%
“…In a study of Troyer citrange regeneration, it was shown that bud sprouting and subsequent shoot formation, facilitated by addition of BA, was significantly increased by light (Moreira- Dias et al 2000). According to Dunstan et al (1985) high cytokinin concentrations stimulated adventitious shoot formation but caused harmful effects on explant quality. Therefore, for further establishment of double-stage culture system, node explants were cultured under 16/8 h photoperiod and BA concentration was reduced.…”
Section: Resultsmentioning
confidence: 96%
“…Increased number of shoots reported by several investigators using BAP (Gleddie et al, 1983;Sarma and Rajam, 1995), Zeatin (Gleddie et al, 1983;Mukherjee et al, 1991) and TDZ (Magioli et al, 1998). The exposure to high concentration of cytokinins for extended periods resulted in new shoots became shorter, stunted and leaf size decreased, this type of problems were experienced by Dunstan et al (1985) in apple. We used proximal end to get connected with the medium and shoots are induced at the proximal end of leaf because high frequency shoot induction at the proximal region may also be due to the higher level of IAA and abscisic acid (Rajasekharan et al, 1987).…”
Section: Discussionmentioning
confidence: 99%